Optimalisasi Pendistribusian ZIS dalam Pengentasan Kemiskinan Berdasarkan Perspektif Maqashid Syariah di Baznas Kota Bogor - Eka Zulianna; Prima Dwi Priyatno (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
Along with the increasing poverty rate from year to year, the Bogor City Baznas also contributes to poverty alleviation efforts, especially in the Bogor City area by directing several distribution programs. However, in reality, the poverty rate in Bogor is increasing. This study aims to understand how the Bogor City Baznas take steps to optimize the distribution of ZIS in an effort to reduce poverty based on the maqashid sharia perspective. This research is expected to be a source of scientific references and academic contributions, and can provide an overview in the field for LAZ institutions and regulators in the field of ZIS distribution as a reference for better future performance. This study uses a qualitative method with a descriptive analysis approach. The results of this study indicate that the steps taken by Baznas in Bogor City to optimize the distribution of ZIS is to classify or classify the needs of mustahik based on their income, so that the nominal ZIS funds distributed have been arranged according to their needs. Furthermore, based on the indicators of maqashid sharia, there is 1 (one) indicator of the five levels of maqashid that has not been fulfilled optimally. However, overall, the ZIS distribution program in an effort to alleviate poverty by the Bogor City Baznas can be stated to have fulfilled the five levels of maqashid sharia.